Self-esteem and teacher self-concept - Sebastián, Victor Hugo (2012)
A reflection on two aspects to be considered in the educational system is made: the self-esteem and self-concept of the teachers. People with positive self-esteem and proper self-concept are able to undertake big tasks, not only at the professional level, but also at the family and social level. The teacher who has built self-esteem and self-concept to own them under certain situations, will make them part of his being and professional work, projecting in his/her educational work and from his/her personality, essential aspects of a quality education. Recognizing the importance of looking at oneself will help to accompany the development of his/her students as persons of good for society.